Carbon dioxide emissions and heavy metal contamination analysis of stone mastic asphalt mixtures produced with high rates of different waste materials - Fernandes, Sara Raquel Marques (2019)
The incorporation of waste materials in asphalt mixtures has driven several studies mainly focused on improving their mechanical performance while minimizing the use of virgin materials. However, these could only be considered cleaner solutions for road paving works if their production and application do not present additional risks for human health and the environment. Therefore, this study aims at assessing the carbon dioxide emissions and possible leachates of stone mastic asphalt mixtures produced with high rates of different waste materials for binder modification or material recycling. Thus, a chemical analysis of eluates that were in contact with those mixtures and an estimation of the carbon dioxide emissions associated with their production and transportation were carried out under different scenarios. In conclusion, these mixtures comply with the established specifications for hazardous leachates. The addition of waste materials to these mixtures decreases carbon dioxide emissions, especially for recycled stone mastic asphalt mixtures with 50% reclaimed asphalt pavement material and bitumens modified with waste materials. Thus, the studied mixtures are innovative solutions for future use in pavement maintenance and rehabilitation operations, in line with the circular economy concept.